ANALISIS STRATEGI BBRSAING CV MICONOS TRANSDATA NUSANTARA DALAM INDUSTRI MIKROSKOP DIGITAL UNTUK KEPERLUAN KHUSUS - , Dwi Purwana, Prof. Dr. Goedono, MBA., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT Miconos Transdata Nusantara is a manufacturing company in the electronic industry in particular in the field of digital microscope for special purposes. CV Miconos Transdata Nusantara is listed as the official equipment manufacturer biomedicine semi automatic high precision in Indonesia, as well as being one of the developers of the microscope and the server network model for special purposes. The main research CV Miconos Transdata Nusantara include developing sensors for special purposes (microscope) as well as its integration of computer networks. Strategic issues problems faced by CV Miconos Transdata Nusantara is increasingly growing number of the competitors in the same industry and CV Miconos Transdata Nusantara management not have a clearly strategy to compete. As a company that oriented to continue the growth, may CV Miconos Transdata Nusantara need to have a competitive strategy to be able to continue to grow and compete in the future. Research design used in this research is a descriptive. The study is to analyze the strategy compete of the company based on the characteristic internal and external environment of the company (IFAS and EFAS). Where the data collected, it is reliable and up to date, and the collected data will be analyzed using SWOT and QSPM. Based on the results of the analysis can be drawn a conclusion, in terms of internal strategy factors for CV Miconos Transdata Nusantara is less capable to utilize its power to overcome the weaknesses, and in terms of external factors the company is able to respond the opportunities and anticipate external threats. Proper strategy to be applied in conditions like this is the strategy hold and maintain, where the choice of an alternative strategy is market penetration and product development. Competitive strategy selection priority of CV Miconos Transdata Nusantara is a strategy WO (Weaknesses Opportunities), This strategy aimed at improving internal weakness in CV Miconos Transdata Nusantara to more take advantage from external opportunities.